2017
DOI: 10.1553/eco.mont-9-2s52
|View full text |Cite
|
Sign up to set email alerts
|

Whitewater recreationists’ preferences for social, resource and managerial attributes in the Alpine Nature and Geopark Styrian Eisenwurzen

Abstract: The Salza River is located in the Alpine Nature and Geopark Styrian Eisenwurzen and is used heavily for whitewater recreation. One of the main goals of protected area management is to provide opportunities for outdoor recreation to maintain or enhance the quality of visitor experience. This study explored whitewater recreationists' crowding perceptions and preferences for river trip scenarios on the Salza River, Austria, using a discrete choice experiment. Six attributes described social, resource and manageri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The rivers provide different river trip experiences based on river difficulty and were located either in urban-proximate or remote areas (Kainzinger et al 2016, 2017) (Table 1). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rivers provide different river trip experiences based on river difficulty and were located either in urban-proximate or remote areas (Kainzinger et al 2016, 2017) (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…From a management perspective, this indicates non-local whitewater boaters might have other motivations, such as challenge (Galloway 2012), rather than the whitewater location itself. Resource managers should also fully understand potential users to their rivers, which can allow whitewater boaters choose a river based on their preferences and skill levels (Kainzinger et al 2016, 2017). …”
Section: Management Implications and Conclusionmentioning
confidence: 99%
“…Many studies have found that visitors to natural areas prefer low use levels [18][19][20][21][22]. Recreation research has often analyzed water-based river recreation use such as canoeing or kayaking [19,[22][23][24], while studies on preferences for visitor use levels of terrestrial riverscape visitors are rare. The majority of water-based recreational studies have found that water-based users prefer low use levels.…”
Section: Human Preferences For Social Conditions On Recreational Trailsmentioning
confidence: 99%
“…Many respondents reported that the number of visitors to the Lobau on Sundays was too high. Most studies using image-based DCEs in the fields of outdoor recreation and landscape preference stressed the important role of visitor numbers in respondents' choices [4,15,16,18,23,24,44]. However, the findings are mixed.…”
Section: Preferences For Social Conditions On Trailsmentioning
confidence: 99%
“…For example, a recreational area may only allow access through ticket sales at particular gates or may only be accessible via a guided tour, which would allow counting based upon ticket or tour sales. These methods have been used in many areas to obtain not only visitor counts, [15][16][17], but also socio-demographic changes in visitor use (e.g., [18]), visitor use in protected areas (e.g., [19]), and evaluations of user recreation fees in the U.S. Forest Service (e.g., [20][21][22]).…”
Section: Direct Countingmentioning
confidence: 99%